Effect of V-Y plasty on lip lengthening and treatment of gummy smile - Dilaver, Emrah; Uçkan, İbrahim Sina (Churchill Livingstone, 2018)
The aim of this study was to assess the effect of isolated V-Y plasty on lip lengthening and the treatment of gummy smile. An isolated V-Y plasty was performed on 14 patients with a gummy smile. In each case, measurements of upper lip length and gingival display were recorded from posed-smile photographs taken preoperatively and at 1, 3, and 6 months postoperatively. Gingival display decreased significantly and lip length increased significantly over all intervals investigated. Applying this technique after Le Fort I surgery may be beneficial; however, as with other injection or surgical lip lengthening methods, its stand-alone application should be questioned.
WOS: 000424716400007
PubMed ID: 29042176
Keywords: Gingival Display; Upper Lip Length; Isolated V-Y Plasty